Trust in science during the COVID-19 pandemic: A typology of internet users in South Africa - Anne Reif; Lars Guenther; Monika Taddicken; Peter Weingart (PLoS ONE, 2026)
The COVID-19 pandemic has underscored the importance of public trust in science, particularly in contexts with diverse cultural backgrounds such as South Africa. Given the increasing reliance on digital science communication and the formation of sub-publics, understanding how different groups of individuals perceive and trust science in this unique setting is crucial for developing effective communication strategies and addressing potential challenges to public trust. This study investigates South Africans’ trust in science and contact with science, as well as perceived changes in trust in science due to the COVID-19 pandemic. Through a survey among South African online users and latent profile analysis, we identified four population groups ( n = 1,541) with varying levels of trust and frequency of contact with science: the fully trusting (30%) , highly trusting (35%) , moderately trusting (28%) , and rather untrusting (8%) . Differences in the patterns regarding the five theoretically derived dimensions of trust in science, namely expertise, integrity, benevolence, transparency and dialogue orientation, are subtle: Those who trust the most have particularly high values for benevolence; those who trust less place their highest value on expertise. Variations in self-perceived changes in trust in science resulting from the COVID-19 pandemic suggest differences among groups in how they interpret science communication. This could inform the development of targeted communication strategies. Furthermore, the results point to cultural specifics and indicate that the COVID-19 pandemic has been a key event for public trust in science in South Africa.